2000
DOI: 10.1034/j.1600-0757.2000.2240109.x
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue elements as diagnostic aids in periodontology

Abstract: Glycosaminoglycans. Glycosaminoglycan are covalently bound to core proteins and they are all sulfated, with the exception of hyaluronan, which exists unattached to a core protein (131) and is not sulfated. Glycosaminoglycans are defined as linear polysaccharide units consisting of repeating disaccharide units of which one is a hexosamine (either D-glucosamine or D-galactosamine) and the other a hexuronic acid (Dglucuronic acid, L-galacturonic acid or iduronic acid). The only exception is keratan sulfate, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 122 publications
(175 reference statements)
0
49
1
Order By: Relevance
“…Cell Culture: Establishment and serial cultivation of IHGKs has been reviewed recently [16]. To avoid medium-derived induction of keratinocyte differentiation, the IHGKs were maintained in lowcalcium keratinocyte growth medium (basal keratinocyte medium, KGM, with provided supplements, Promocell, Heidelberg, Germany), containing 50 mg ml À1 kanamycin (Roche Diagnostics, Mannheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell Culture: Establishment and serial cultivation of IHGKs has been reviewed recently [16]. To avoid medium-derived induction of keratinocyte differentiation, the IHGKs were maintained in lowcalcium keratinocyte growth medium (basal keratinocyte medium, KGM, with provided supplements, Promocell, Heidelberg, Germany), containing 50 mg ml À1 kanamycin (Roche Diagnostics, Mannheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…[15] Contrasting its corresponding epithelium, the CT is poorly populated by cells, while it mainly consists of extracellular-matrix (ECM) molecules including various collagens, FN and a variety of proteoglycans. [16] These CT matrix components which, as a base substance, constitute the cells' microenvironment are synthesized by the cells themselves prior to secretion. Thus, CT fibroblasts produce multiple collagens, among which collagen type-I is the most abundant matrix molecule in the CT.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding noncollagenous organic matrices of the cementum, immunohistochemistry and biochemistry have identified many distinct molecules, including noncollagenous glycoproteins, proteoglycans, plasma-derived macromolecules, and several growth factors (for reviews, see Embery et al 2000;Waddington and Embery 2001;Bosshardt 2005), and have shown that two noncollagenous glycoproteins, bone sialoprotein (BSP) and osteopontin (OPN), are major constituents of the noncollagenous matrices (McKee et al 1996;Bosshardt et al 1998;Nanci 1999;Bosshardt 2005). The BSP and OPN are closely associated with mineralization, matrix-matrix attachment, and cell-cell/matrix attachment in collagen-based hard tissues (for reviews, see Ganss et al 1999;Sodek et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] It is a complex mixture of substances derived from serum, leukocytes, structural cells of the periodontium, and oral bacteria. 25 In health, GCF represents a transudate of gingival tissue interstitial fluid; however, as gingivitis and periodontitis develop, GCF becomes true inflammatory exudate.…”
Section: Introductionmentioning
confidence: 99%